Pengaruh Personal Hygiene Terhadap Kejadian Penyakit Skabies - Muhammad Panji Marga (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Scabies is a skin disease caused by infestation and sensitization of the Sarcoptes scabiei v. Hominis mite that occurs in communities, groups, or families living in a dense, low economy, and low knowledge. Maintenance of personal hygiene strongly determines the health status, where the individual consciously and on the personal initiative to maintain health dan prevent disease. Objective: Know more about the personal effect of hygiene on the incidence of scabies. Methods: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results: There is a meaningful influence between personal hygiene habits and the incidence of scabies. Conclusion: There is a significant connection between a person’s personal hygiene with the incidence of scabies.